1999
DOI: 10.1111/j.1600-0773.1999.tb02015.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Ceruloplasmin, Superoxide Dismutase and Iron Parameters in Parkinson's Disease

Abstract: Abstract:In a previous study we found copper dyshomeostasis in patients with Alzheimer's disease. In this study, levels of copper in plasma, of ceruloplasmin in serum and ceruloplasmin oxidative activity as well as superoxide dismutase (SOD) activity in erythrocytes were determined in 40 patients with Parkinson's disease and their healthy age-and gendermatched controls. Copper concentrations did not differ significantly in the two groups, whereas both ceruloplasmin concentrations and ceruloplasmin oxidative ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
2
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 18 publications
8
74
2
4
Order By: Relevance
“…Tó rsdó ttir et al 1999). Since ceruloplasmin is also expressed at least in some types of astrocytes in the brain (Klomp & Gitlin 1996) the enzyme must therefore be considered to have antioxidant function in brain or the central nervous system in general as well as in serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tó rsdó ttir et al 1999). Since ceruloplasmin is also expressed at least in some types of astrocytes in the brain (Klomp & Gitlin 1996) the enzyme must therefore be considered to have antioxidant function in brain or the central nervous system in general as well as in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Copper concentration in plasma on the other hand was in both studies within normal limits in patient groups and the controls. It was therefore concluded that a kind of copper dyshomeostasis prevailed in these degenerative diseases of the central nervous system since the synthesis of the enzyme proteins or the mechanism of incorporation of the copper atoms into the molecules, or both, were defective (Snaedal et al 1998, Tó rsdó ttir et al 1999). The present results extend these studies to include the third neurodegenerative disease, amyotrophic lateral sclerosis.…”
mentioning
confidence: 99%
“…This association is dependent on the duration of Al exposure and only becomes significant if an individual has resided in an area with high Al in drinking water (> 100 Ag/L) for several years. Homeostatic alterations in brain Cu levels have also been implicated in the pathogenesis of several neurological disorders including Alzheimer's, Parkinson's and prion diseases (Torsdottir et al, 1999;Mercer, 2001;Brown and Kozlowski, 2004). The toxicity of excess Cu is best demonstrated by the heritable disorder, Wilson's disease, in which the liver is unable to excrete the metal and thus there is tissue accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has demonstrated that oxidative stress plays a seminal role in the pathology of several neurological diseases, including Alzheimer's disease [62,63] , Down's syndrome [64] , Parkinson's disease [65,66] , schizophrenia [67,68] andbipolar affective disorder [69] . Interestingly, recent studies have reported increased free-radicals, lower levels of antioxidant proteins andgreater oxidatively modified biomolecules in peripheral samples from autistic children [70][71][72][73][74][75][76][77] .…”
Section: Indications Of Oxidative Stress In Autismmentioning
confidence: 99%